Mutational profile by targeted next generation sequencing of non-small cell lung cancer in the Mexican population - Norma Hernández-Pedro; Giovanny Soca-Chafre; Carmen Alaez-Versón; Karol Carrillo-Sánchez; Alejandro Avilés-Salas; Edgar Vergara; Oscar Arrieta (Instituto Nacional de Salud Pública, 2019)
Objective. Targeted next-generation sequencing (t-NGS) has revolutionized clinical diagnosis allowing multiplexed detection of genomic alterations. This study evaluated the profile of somatic mutations by t-NGS in Mexican patients with non-small cell lung cancer (NSCLC). Materials and methods. Genomic DNA was extracted from 90 lung adenocarcinomas and sequences were generated for a panel of 48 cancer genes. Epidermal Growth Factor Receptor (EGFR) mutations were detected in parallel by quantitative PCR. Results. The mutational profile of NSCLC revealed alterations in 27 genes, where TP53 (47.8%) and EGFR (36.7%) exhibited the highest mutation rates. EGFR Q787 mutations were present in 14 cases (15.6%), 10 cases had exon 19 deletions (11.1%), seven cases had L858R (7.8%). The mutational frequency for genes like EGFR, MET, HNF1A, HER2 and GUSB was different compared to caucasian population. Conclusion. t-NGS improved NSCLC treatments efficacy due to its sensitivity and specificity. A distinct pattern of somatic mutations was found in Mexican population.